Assessment of the Applicability of Failure Frequency Models for Dense Phase Carbon Dioxide Pipelines. (August 2019) - Lyons, C.J.; Race, J.M.; Wetenhall, B.; Chang, E.; Hopkins, H.F.; Barnett, J.
Highlights: Existing oil and gas pipeline third-party external interference failure frequency models have been reviewed to assess whether they could be applied to dense phase CO2 pipelines. It was found that the high design pressure requirement for a dense phase CO2 pipeline typically necessitates the use of high wall thickness linepipe in pipeline construction. The research indicates that wall thickness of typical dense phase CO2 pipelines is beyond the known range of applicability for the pipeline failure equations used within existing failure frequency models. There is a limitation to existing UK fault databases with regards to their application to CO2 pipelines because there are currently no dense phase CO2 pipelines operating in the UK. Further work needs to be conducted to confirm the most appropriate approach for calculating failure frequency for dense phase CO2 pipelines. It is recommended that a new failure frequency model suitable for dense phase CO2 pipelines is developed that can be readily updated to the fault database version Abstract: In Carbon Capture, Usage and Storage (CCUS) schemes, Carbon Dioxide (CO2 ) is captured from large scale industrial emitters and transported to geological sites for storage. The most efficient method for the transportation of CO2 is via pipeline in the dense phase. CO2 is a hazardous substance which, in the unlikely event of an accidental release, could cause people harm. To correspond with United Kingdom (UK) safety legislation, the design and construction of proposed CO2 pipelines requires compliance with recognised pipeline codes. The UK code PD-8010-1 defines the separation distance between a hazardous pipeline and a nearby population as the minimum distance to occupied buildings using a substance factor. The value of the substance factor should be supported by the results of a Quantitative Risk Assessment (QRA) approach to ensure the safe design, construction and operation of a dense phase CO2 pipeline. Failure frequency models are a major part of this QRA approach and the focus of this paper is a review of existing oil and gas pipeline third-party external interference failure frequency models to assess whether they could be applied to dense phase CO2 pipelines. It was found that the high design pressure requirement for a dense phase CO2 pipeline typically necessitates the use of high wall thickness linepipe in pipeline construction; and that the wall thickness of typical dense phase CO2 pipelines is beyond the known range of applicability for the pipeline failure equations used within existing failure frequency models. Furthermore, even though third party external interference failure frequency is not sensitive to the product that a pipeline transports, there is however a limitation to the application of existing UK fault databases with to onshore CO2 pipelines as there are currently no dense phase CO2 pipelines operating in the UK. Further work needs to be conducted to confirm the most appropriate approach for calculating failure frequency for dense phase CO2 pipelines, and it is recommended that a new failure frequency model suitable for dense phase CO2 pipelines is developed that can be readily updated to the latest version of the fault database.